Pengaruh Perilaku Gemar Menonton Film Horor terhadap Gangguan Emosional Anak Menjelang Usia Baligh di SDN 11 Limboto - Suhendra Iskandar (Universitas Negeri Makassar, 2020)
Research on the effect of watching horror films on emotional disturbances of early-adult (10 - 12 years old) was observed in four areas, sleep health, mind cleanliness, independence, and openness in trying new things. A total of 80 samples were divided into 3 groups, 36 samples in the horror movie maniac group, 11 samples in the horror movie audience group, and 33 samples in the non-horror movie audience group. Data for the analysis of sleep health, independence, and openness in trying new things was collected through questionnaire and observation methods, while for the analysis of mind hygiene was collected through the method of image psychology tests. Data for sleep health and mind cleanliness was analyzed through the chi-square method (λ2), while for independence and openness in trying new things was analyzed through the one-way ANOVA method. The results show that the behavior of watching horror films in children approaching baligh age causes emotional disturbances in the realm of sleep health and mind hygiene, but did not have a significant impact on the realm of independence and openness in trying new things.